Measuring connectedness of Euro area sovereign risk - Rebekka Gätjen; Melanie Schienle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
We introduce a methodology for measuring default risk connectedness that is based on an out-of-sample variance decomposition of model forecast errors. The out-of-sample nature of the procedure leads to "realized" measures which, in practice, respond more quickly to crisis occurrences than those based on in-sample methods. The resulting relative and absolute connectedness measures find distinct and complementary information from CDS and bond yield data on European area sovereign risk. The detection and use of these second moment di erences of CDS and bond data is new to the literature and allows to identify countries that impose risk on the system from those which sustain risk.
Keywords: C32; C58; F34; G01; G18; 330; sovereign risk measurement; variance decomposition; connectedness; CDS and bond spreads; financial and eurozone crisis